Human Papillomavirus Is Associated With Adenocarcinoma of Lung: A Population-Based Cohort Study - Huang, Jing-Yang; Lin, Chuck; Tsai, Stella Chin-Shaw; Lin, Frank Cheau-Feng (Frontiers in Medicine, 2022)
Abstract Background: Recent trends in the incidence of lung cancer have been reported despite the decreasing rate of smoking. Lung cancer is ranked among the top causes of cancer-related deaths. The ratio of adenocarcinoma to squamous cell carcinoma, as well as the ratio of women to men, is still increasing. Human papillomavirus (HPV) has been discovered in lung cancer tissues and blood specimens, particularly in Eastern countries. However, the association between HPV infection and lung adenocarcinoma remains unclear. Methods: This population-based cohort study was conducted using data from Taiwan’s single-payer national health insurance and cancer registry databases. HPV infection, cancer, sex, age, comorbidities, urbanization, and occupation data were collected. The cumulative incidence rates were generated using Kaplan-Meier curves and log-rank tests. COX regression analysis was used to estimate the hazard ratios of factors associated with cancer occurrence. We used data from 2007 and 2015. The cases were matched with sex and age in a 1:2 manner with 939,874 HPV+ and 1,879,748 HPV− individuals, respectively. Results: The adjusted hazard ratios [95% confidence interval (CI)] for HPV infection in all lung cancers were 1.539 (1.436-1.649), male lung cancer 1.434 (1.312-1.566), female lung cancer 1.742 (1.557-1.948), squamous cell carcinoma (SCC) 1.092 (0.903-1.320), male SCC 1.092 (0.903-1.320), female SCC 0.949 (0.773-1.164), adenocarcinoma 1.714 (1.572-1.870), male adenocarcinoma 1.646 (1.458-1.858), and female adenocarcinoma 1.646 (1.458-1.858). The highest adjusted hazard ratio for lung cancer was chronic obstructive pulmonary disease (COPD) 1.799 (1.613-2.007), followed by male sex 1.567 (1.451-6.863) and HPV infection. The highest adjusted hazard ratio for adenocarcinoma was HPV infection 1.714 (1.572-1.870), followed by COPD 1.300 (1.102-1.533); and for SCC, male sex 5.645 (4.43-3.37) followed by COPD 2.528 (2.002-3.192). Conclusion: Our study showed that HPV infection was associated with the occurrence of adenocarcinoma of the lung in both men and women, but not associated with SCC of the lung.